Mutant p53 and Twist1 Co-Expression Predicts Poor Prognosis and Is an Independent Prognostic Factor in Breast Cancer - Zhang, Yong-Qu; Zhang, Fan; Zeng, Yun-Zhu; Chen, Min; Huang, Wen-He; Wu, Jun-Dong; Chen, Wei-Ling; Gao, Wen-Liang; Bai, Jing-Wen; Yang, Rui-Qin; Zeng, Huan-Cheng; Wei, Xiao-Long; et al. (Frontiers in Oncology, 2021)
Purpose: Both Twist1, the basic Helix-Loop-Helix transcription factor (bHLH) transcription factor, plays a key role in the embryonic development and tumorigenesis p53, a frequently mutated tumor suppressor in cancer, play a key and significant role in breast cancer tumorigenesis. However, the regulation mechanism and clinical signification when they are co-expressed are remains unclear in breast cancer. The purpose of this study was to analyze whether the co-expression of Twist1 and mutant p53 could be a potential marker to predict patient prognosis in this disease. Methods: The expression of Twist1 and mutant p53 were evaluated by immunohistochemistry from 408 breast cancer patients. The mRNA levels in breast cancer were analyzed through the ONCOMINE database. Kaplan-Meier Plotter, was used to analyze the correlation between Twist1with wild-type or mutant p53 expression and prognosis with respect to recurrence-free survival (RFS) and overall survival (OS) in breast cancer patients. Results: Of the 408 patients enrolled, 237(58%) had high expression of mutant p53.While, Two-hundred and twenty patients (53.9%) showed Twist1 positive immunostaining, and 188 cases were Twist1 negative. Analysis from ONCOMINE revealed that Twist1 and mutant p53 mRNA were highly correlated (P<0.001). Furthermore, patients with co-expressions of Twist1 and mutant p53 (T+P+) had significantly advanced clinical stage III 61/89, 68.5% in (T+P+) group VS. stage III 28/89,31.5% in (T-P-) group , stage II 63/104,60.6% in (T+P+) group VS. 41/104, 39.4% in (T-P-) group but negatively related with early stage in stage I and stage 0 (P=0.039), worse DFS ( P = 0.017) and OS ( P=0.048). Univariate and multivariate analysis demonstrated three variables: lymph node involvement, larger tumor and T+P+ were independent prognostic factors for DFS and two variables: node involvement and T+P+ were two independent factors for OS in this cohort. Total risk scores and nomograms were considered to be trustworthy for predicting DFS and OS in breast cancer patients. Conclusions: Our results revealed that co-expression of mutant p53 and Twist1 was associated with advanced clinical stage, TNBC subtype, distant metastasis and shorter DFS/OS in breast cancer patients. Co-evaluation of mutant p53 and Twist1 might be an appropriate tool for predicting breast cancer patient outcome.